Hygienization and control of Diplodia seriata fungus in vine pruning waste composting and its seasonal variability in open and closed systems - Matei, Petruta M (Waste management (New York, N.Y.), 2016)
Copyright © 2016 Elsevier Ltd. All rights reserved.